miRNAs in NK Cell-Based Immune Responses and Cancer Immunotherapy - Pesce, Silvia; Greppi, Marco; Ferretti, Elisa; Obino, Valentina; Carlomagno, Simona; Rutigliani, Mariangela; Thoren, Fredrik B.; Sivori, Simona; Castagnola, Patrizio; Candiani, Simona; Marcenaro, Emanuela (Frontiers in Cell and Developmental Biology, 2020)
The incidence of certain forms of tumors has increased progressively in recent years and is expected to continue growing as life expectancy continues to increase. Tumor-infiltrating NK cells may contribute to develop an anti-tumor response. Optimized combinations of different cancer therapies,, including NK cell-based approaches for targeting tumor cells, have the potential to open new avenues in cancer immunotherapy. Functional inhibitory receptors on NK cells are needed to prevent their attack on healthy cells. Nevertheless disruption of inhibitory receptors function on NK cells increases the cytotoxic capacity of NK cells against cancer cells. MicroRNAs (miRNAs) are small non-coding RNA molecules that target mRNA and thus regulate the expression of genes involved in the development, maturation, and effector functions of NK cells. Therapeutic strategies that target the regulatory effects of miRNAs have the potential to improve the efficiency of cancer immunotherapy. Interestingly, emerging evidence points out that some miRNAs can, directly and indirectly, control the surface expression of immune checkpoints on NK cells or that of their ligands on tumor cells. This suggests a possible use of miRNAs in the context of anti-tumor therapy. This review provides the current overview of the connections between miRNAs and regulation of NK cell functions and discusses the potential of these miRNAs as innovative biomarkers/targets for cancer immunotherapy.